Question

Solve the initial-value problem y''+5y'+6y=0, y(0)=1, y′(0)=−1, using Laplace transforms. When writing your answer limit yourself...

Solve the initial-value problem y''+5y'+6y=0, y(0)=1, y′(0)=−1,

using Laplace transforms. When writing your answer limit yourself to showing:

(i) The equation for L(y);

(ii) The partial fraction decomposition;

(iii) The antitransforms that finish the problem.

Homework Answers

Know the answer?
Your Answer:

Post as a guest

Your Name:

What's your source?

Earn Coins

Coins can be redeemed for fabulous gifts.

Not the answer you're looking for?
Ask your own homework help question
Similar Questions
Use the method of Laplace transforms to solve the following initial value problem. y'' + 6y'...
Use the method of Laplace transforms to solve the following initial value problem. y'' + 6y' + 5y = 12e^t ; y(0) = −1, y'(0) = 7
Use Laplace transforms to solve the given initial value problem. y"-2y'+5y=1+t y(0)=0 y’(0)=4
Use Laplace transforms to solve the given initial value problem. y"-2y'+5y=1+t y(0)=0 y’(0)=4
Solve the following initial value problem. y(4) − 6y′′′ + 5y′′  =  2x, y(0)  =  0,...
Solve the following initial value problem. y(4) − 6y′′′ + 5y′′  =  2x, y(0)  =  0, y′(0)  =  0, y′′(0)  =  0, y′′′(0)  =  0. (not using Laplace)
Solve the initial value problem using Laplace transforms y "+ 2ty'-4y = 1; y (0) =...
Solve the initial value problem using Laplace transforms y "+ 2ty'-4y = 1; y (0) = y '(0) = 0.
use Laplace transforms to solve the integral for y(t) y"-6y'+5y=(14-8t)e^t y(0)=3 y'(0)=-4
use Laplace transforms to solve the integral for y(t) y"-6y'+5y=(14-8t)e^t y(0)=3 y'(0)=-4
Solve the given initial-value problem. y'' + 5y' − 6y = 12e2x,    y(0) = 1, y'(0) =...
Solve the given initial-value problem. y'' + 5y' − 6y = 12e2x,    y(0) = 1, y'(0) = 1
Solve the initial value problem below using the method of Laplace transforms. y''-y'-30y=0, y(0) = 4...
Solve the initial value problem below using the method of Laplace transforms. y''-y'-30y=0, y(0) = 4 , y'(0) = 46 y(t) = ?
Use the Laplace transform to solve the following initial value problem: y′′ + 8y ′+ 16y...
Use the Laplace transform to solve the following initial value problem: y′′ + 8y ′+ 16y = 0 y(0) = −3 , y′(0) = −3 First, using Y for the Laplace transform of y(t)y, i.e., Y=L{y(t)}, find the equation you get by taking the Laplace transform of the differential equation __________________________ = 0 Now solve for Y(s) = ______________________________ and write the above answer in its partial fraction decomposition, Y(s) = A / (s+a) + B / ((s+a)^2) Y(s) =...
solve the given initial value problem y''-5y'+6y=0, y(0)=3/5, y'(0)=1
solve the given initial value problem y''-5y'+6y=0, y(0)=3/5, y'(0)=1
Solve the initial value problem below using the method of Laplace transforms. y"+11y'+30y=280e^2t, y(0)=1, y'(0)=32
Solve the initial value problem below using the method of Laplace transforms. y"+11y'+30y=280e^2t, y(0)=1, y'(0)=32
ADVERTISEMENT
Need Online Homework Help?

Get Answers For Free
Most questions answered within 1 hours.

Ask a Question
ADVERTISEMENT